2004
DOI: 10.1158/1078-0432.ccr-03-0510
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of 14-3-3σ Is Associated with Advanced Disease in Human Epithelial Ovarian Cancer

Abstract: Purpose: In this study, we examined the promoter methylation status and expression of 14-3-3 and evaluated its clinical significance in epithelial ovarian cancer.Experimental Design: Twelve ovarian cancer cell lines; 2 ovarian surface epithelial cell lines; and 8 normal, 8 benign, 12 borderline, and 102 ovarian cancer tissues were examined. Methylation-specific PCR, quantitative reverse transcription-PCR, and immunohistochemistry were used to evaluate methylation status and expression of 14-3-3 gene and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 31 publications
(32 reference statements)
3
80
1
Order By: Relevance
“…This rate of negative cases was higher than that found in our studies of other gynecological cancers (i.e., ovarian serous adenocarcinoma, 26.5%; endometrial endometrioid adenocarcinoma, 24.7%) (Akahira et al 2004;Ito et al 2005). We designated tissues with > 50% UPSC as "pure" (37/51 patients, 72.5%) and those with 10-50% UPSC and ≥ 10% of other components as "mixed" (14/51 patients, 27.5%).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This rate of negative cases was higher than that found in our studies of other gynecological cancers (i.e., ovarian serous adenocarcinoma, 26.5%; endometrial endometrioid adenocarcinoma, 24.7%) (Akahira et al 2004;Ito et al 2005). We designated tissues with > 50% UPSC as "pure" (37/51 patients, 72.5%) and those with 10-50% UPSC and ≥ 10% of other components as "mixed" (14/51 patients, 27.5%).…”
Section: Discussioncontrasting
confidence: 74%
“…Loss of 14-3-3σ protein is also evident in prostate carcinoma and its precursors (Cheng et al 2004;Urano et al 2004). Akahira et al (2004) showed that loss of 14-3-3σ expression correlated with advanced disease and/or high grade histology and was significantly associated with a poor prognosis in epithelial ovarian carcinoma. Finally, decreased immunoreactive 14-3-3σ is significantly associated with poor prognosis and/ or recurrence in endometrial endometrioid adenocarcinoma (Ito et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of 14-3-3σ expression in association with hypermethylation has also been reported in several other cancers, including ovarian [8], hepatocellular [9], prostate [10], some lung [11], gastric [12] and endometrial carcinomas [13]. It is important to point out that this is not the only mechanism for 14-3-3σ down-regulation.…”
Section: Introductionmentioning
confidence: 87%
“…Seven different isoforms have been identified in mammalian cells, with each isoform having distinct tissue localization and function. Amongst the various 14-3-3 isoforms, 14-3-3 sigma is differentially expressed in cancers of breast, lung, prostate and ovary (9)(10)(11)(12). Qi et al (13) have shown elevated levels of beta, gamma, sigma and theta isoforms of 14-3-3 in human lung cancer.…”
Section: Introductionmentioning
confidence: 99%